The Economics of Death and Funeral Celebration in a Ghanaian Akan Community - Dei, George J. S. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1989)
This study examines the economic aspects of death and funeral celebration in the Akan town of Ayirebi, near Akyem Oda, in southeastem Ghana. It illustrates the extent of social responsibility that exists in a contemporary stratified society that has a mixed form of property holding. It shows how a traditional institution functions as an effective response to socioeconomic stress, alleviating the hardships of the poorer segments of the population while allowing local capitalists to assert status and prestige. The examination of the processes involved in the preparation of the corpse, burial and observance of the final funeral rites, as well as what happens to productive resources after the owner’s death, shows an elaborate division of labour, and economic costs and benefits within the bereaved family, the lineage and the wider community.